The prevalence of retinopathy in patients with type 1 diabetes treated with education-based intensified insulin therapy and its association with parameters of glucose control. (February 2019) - Hatz, Katja; Minder, Anna Elisabeth; Lehmann, Roger; Drescher, Tilman; Gerendas, Bianca; Schmidt-Erfurth, Ursula; Kaider, Alexandra; Pruente, Christian; Zulewski, Henryk
Abstract: Aim: Prevalence of retinopathy (DR) in patients with type 1 diabetes treated with education-based intensified insulin therapy (EBIIT) and its association with parameters of glucose control. Methods: 151 patients with mean diabetes duration of 14.3 years [SD ± 5.8]) were analyzed. Eyes were examined using standardized 7 field ETDRS (Early Treatment Diabetic Retinopathy Study) settings and images analyzed by a professional external reading center. The glucose exposure over time was defined as HbA1c years, i.e. the sum of the differences between annual mean HbA1c (in %) minus the ideal HbA1c of 6.0% (42 mmol/mol) for each diabetes year (e.g. HbA1c of 8% (64 mmol/mol) over 6 years gives an excess HbA1c of 2.0% (22 for mmol/mol) for 6 years, resulting in 12 HbA1c years (or 131 for mmol/mol)). Results: The median (interquartile range) of individual mean HbA1c was 7.3% (6.8–7.8) [56 mmol/mol (51–62)]. and the median HbA1c years was 16.8 (9.1–29.1) [183 mmol/mol (99–319)]. No evidence for DR was found in 59 patients (39%), stage 1 DR in 43 (28.5%), stage 2 in 41 (27.2%), stage 3 in 7 (4.6%) and proliferative DR stage 4 in 1 patient. The best correlation between severity of DR and diabetes control measures was found for HbA1c years (Pearson r = 0.41, p < 0.001). Conclusions: In type 1 diabetes EBIIT is associated with good diabetes control and a low prevalence of DR. The cumulative glucose exposure over time given as HbA1c years is the best predictor for development of DR. ClinicalTrials.gov Identifier: NCT02307110.